Pré e pós-tratamento por eletro-oxidação associada à fotocatálise heterogênea em uma ETA por filtração direta visando a redução dos precursores dos compostos organoclorados - Abdala Neto, Eliezer Fares (2012)
This study evaluated the performance of the heterogeneous photocatalysis combined with electrooxidation compounding a hybrid photoreactor (contact time: 2.75; 5.5 and 11 min.) to pre-treat eutrophic water, comparing the use of chlorine (5 and 10 mg.L-1) and chlorine dioxide (1.2 mg.L-1), subjected to descending direct filtration (aluminum hydroxychloride at 5.4 mg.L-1 and polymer polyDADMAC at 2.0 mg.L-1). It was also evaluated the photoreactor in the post-treatment of water pre-oxidized with chlorine and chlorine dioxide. The photoreactor was equipped with Vacuum-UV sources (photoactivating immobilized TiO2) and set of metal electrodes (7.33 mA.cm-2). The quality of the treated water was analyzed regarding the reduction in concentration of organochlorine precursors, especially COD, chlorophyll-a, and the formation of total trihalomethanes and total haloacetic acids. The analyses followed the guidelines of the Standard Methods for Examination of Water and Wastewater (APHA, 2005). The photoreactor as an alternative for pre-oxidation has promoted the best mean results of removal reaching for turbidity 99.50%, 97.5% for the apparent color, 98.89% for chlorophyll-a, and 65.47% for COD. Meanwhile by using the chemical pre-oxidation, the removal of apparent color was 85.94% and 92.19%, with chlorine and dioxide chlorine, respectively. As regard with turbidity, the result with the use of chlorine was 95.57% and 96.23% with chlorine dioxide. For the COD, the result was 37.45% for chlorine and 49.45% with chlorine dioxide. In relation to chlorophyll, the removal reached 91.94% and 94.04%, with chlorine and dioxide chlorine, respectively. For the remaining concentrations of total trihalomethanes, considering the significant digits as given by the current potability standards in Brazil, Ordinance # 2914 (BRASIL, 2011), with maximum allowable value of 0.1 mg.L-1, all pre-treatment conditions (photoreactor, chlorine and chlorine dioxide) have met this limit, and presented no significant difference between obtained values. As for the average formation of total haloacetic acids, no significant difference was detected between values obtained under different conditions studied, but all values were above the potability limit, reaching for water pre-oxidized with the photoreactor 0.164 mg/L, for water pre-oxidized with chlorine, 0.151 mg/L, and for water pre-oxidized with dioxide chlorine, 0.139 mg/L. The use of the photoreactor in the post-treatment of water pre-oxidized with chlorine or dioxide chlorine has not significantly reduced the concentrations of total trihalomethanes and total haloacetic acids, which were above the limits set by the Ordinance # 2914.